Planned Change: Drivers of High Implementation for a Pedagogical Self-Regulated Learning Intervention - Faith, Laurie Christine; Pyle, Angela (Frontiers in Education, 2021)
Resourcefulness and adaptability are essential to success in the modern economy; the motivation, metacognition, and cognitive skills required for self-regulated learning (SRL) have never been more important. Unfortunately, teacher-led SRL interventions rarely survive implementation, and teachers' general practices rarely reflect their intention to promote SRL. After discussing the shortcomings of virtual or modularized SRL education, this study explores the drivers of a human-led, communal, pedagogical approach. Data was collected over 3 months and three timepoints from 81 kindergarten to Grade 8 teachers who were genuinely dissatisfied by their status quo practices, ready for change, and largely eager to implement the novel teaching approach presented to them. Building on established theories of planned change implementation, this research shows a minimal effect of teachers' approval of the intervention on implementation. Rather, specific drivers to the implementation of complex, communal pedagogical interventions included the support of high-status supervisors and peers, while identified constraints to implementation included fears regarding management of student behavior.